Performance of medicinal plants in the field of anticoccidial drugs - M Torabi Goodarzi; HR Haddadzadeh; SH Shafiei Darabi (Institue of Medicinal Plants, ACECR, 2005)
Coccidiosis is an infection of the intestinal tract caused by protozoan coccidial parasites of the genus Eimeria. A wide rang of vertebrates, can be infected and it is especially prevalent when animals or birds are grouped together in significant numbers. The development of the broiler industry in the 1940s required the urgent availability of Anticoccidial compounds. Intensive screening activities by several companies soon produced a range of medicines that were effective in the control of coccidia. Increasing resistance of coccidia to anticoccidial drugs currently used by the poultry industry has stimulated the search for new method of control. As part of this effort have investigated medicinal plants as a potential source of compounds with anticoccidial activity. This paper reviews about 35 types of anticoccidial medicinal plant and herbal drugs from 1940 until now. These studies indicate that a Larg number of herbal preparations with anticoccidiol proprieties and futher more with stimulation of the imniune system or production of mucus fajer in intestines are very effective in control of coccidiosis.